2011
DOI: 10.1161/atvbaha.111.227892
|View full text |Cite
|
Sign up to set email alerts
|

Rho-Associated Kinase Activity, Endothelial Function, and Cardiovascular Risk Factors

Abstract: Objective-Cardiovascular diseases are associated with chronic activation of Rho-associated kinases (ROCKs) and endothelial dysfunction. Both increased ROCK activity and endothelial dysfunction are thought to be closely associated with conventional cardiovascular risk factors. The purpose of this study was to determine the relationships between ROCK activity, endothelial function, and cardiovascular risk factors. Key Words: endothelial function Ⅲ risk factors Ⅲ Rho-associated kinases R ho-associated kinases (RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 45 publications
1
54
0
Order By: Relevance
“…In healthy subjects as well as those with cardiovascular risk factors but no established cardiovascular or (Soga et al, 2011). This later correlation thus suggests that leukocyte ROCK activity possibly predicts cardiovascular mortality and morbidity.…”
Section: A Cardiovascular Diseasesmentioning
confidence: 79%
“…In healthy subjects as well as those with cardiovascular risk factors but no established cardiovascular or (Soga et al, 2011). This later correlation thus suggests that leukocyte ROCK activity possibly predicts cardiovascular mortality and morbidity.…”
Section: A Cardiovascular Diseasesmentioning
confidence: 79%
“…ROCK1 activity is regulated by small G proteins, such as RhoA, 33 to exert detrimental effects in pathophysiologic conditions, including obesity, cardiovascular diseases, renal fibrosis, and diabetes. [34][35][36] Recently, ROCK1 in mouse models of diabetic nephropathy has been identified as a mechanism causing mitochondrial fission and apoptosis in endothelial cells and podocytes. 32 There are other reports that ROCK1 triggered death-inducing signals in many cells but not in skeletal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…1 Recently, measurement of FMD in the brachial artery using high-resolution ultrasound, as an index of endothelium-dependent vasodilation, has been widely used as a method for assessing endothelial function. [2][3][4][7][8][9] Nitroglycerine-induced vasodilation, an index of endothelium-independent vasodilation, has been assessed as a control test to ensure that impaired FMD is not a result of underlying vascular smooth muscle dysfunction or alterations in vascular structure but truly a consequence of endothelial dysfunction. 16,17 However, it has been shown that nitroglycerine-induced vasodilation per se is impaired in adults with cardiovascular risk factors, or with coronary atherosclerosis and in children at risk for atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%